Advanced Assistive Technologies for Elderly People: A Psychological Perspective on Seniors' Needs and Preferences (part B) - Troncone, Alda; Saturno, Raffaele; Buonanno, Michele; Pugliese, Luca; Cordasco, Gennaro; Vogel, Carl; Esposito, Anna (My University, 2021)
This paper provides a general overview of the literature regarding advanced assistive technologies devoted to improving elders’ life. Recent studies on assistive robots and embodied conversational agents are carefully examined in order to identify main seniors’ preferences regarding their general design. While providing data on seniors’ preferences about the design of assistive devices, main evidence on both robots and virtual agent’s appearance, abilities/functionalities, personalities, and role features are summarized and commented.
PUBLISHED
Keywords: Older user; Assistive technology; Robot; Virtual agent; Design; Preferences; Ageing; Digital Engagement; Digital Humanities; Computational Linguistics; Computational linguistics; computational linguistics